A detailed analysis of the current status of intestinal transplantation in Latin America. Issue 2 (April 2020) - Gondolesi, Gabriel E.; Doeyo, Mariana; Solar-Muñiz, Héctor
Abstract : Purpose of review: Latin America and the Caribbean represent a vast territory, with very different economic and healthcare realities, which result in significant disparities in the management of intestinal failure patients throughout the region. Since 1968, multiple attempts have been done to accomplish a successful intestinal transplant; but it was not until 2004, with the establishment of multidisciplinary programs, that large series with long-term results could be obtained. Currently, three countries (Colombia, Argentina, and Brazil) in the region are actively performing these procedures. Recent findings: A total number of 135 intestinal transplants have been performed; 11 attempts before 2004, and 124 after that period, 66 transplants were done in Argentina (42 in children), 40 in Colombia, 15 in Brazil (1 child), 2 in Costa Rica and 1 in México; 76% have been isolated, whereas 2 were done with living donors. Summary: Publications are still scarce, and compliance to existing registries remains limited. The challenge for the next years is to develop more 'comprehensive units' and extend home parenteral nutrition availability in the rest of the region. Regional cooperation and networking need to be set, in order to achieve regional self-sufficiency and improve long-term results.